Bowl: Anyam Technique on Ceramic - Sudiyati, Noor (Institut Seni Indonesia Yogyakarta, 2023)
Adding value to works of art is the subject of many discussions, and finding a new aesthetic can be accomplished by innovation and experimenting with the medium and techniques employed. This research attempts to make ceramics utilizing various embodied approaches similar to other manufactured materials. Specifically, bowl-shaped ceramics are formed using a woven technique similar to bamboo and then arranged in an interlocking pattern to resemble woven bamboo. The final result of this application technique is in the form of artistic bowls that have afresh aesthetic value for the development of ceramic art. These bowls are hollow due to the woven fabric and contain many values built-in to ceramic form, including material efficiency, organic form, and artistic form, which was previously unexpected. This serves as an accelerator for future application development of various shaping approaches. This confirms that the creative possibilities for plastic clay are virtually endless.